1984
DOI: 10.1159/000179999
|View full text |Cite
|
Sign up to set email alerts
|

Serum TSH, T<sub>4</sub>, T<sub>3</sub>, FT<sub>4</sub>, FT<sub>3</sub>, rT<sub>3</sub>, and TBG in Youngsters with Non-Ketotic Insulin-Dependent Diabetes mellitus

Abstract: Several parameters of thyroid function were studied in 112 non-ketoacidotic youngsters with insulin-dependent diabetes mellitus (IDDM). Levels of thyroxine (T4), reverse triiodothyronine (rT3), thyroxine-binding globulin (TBG) and T3 were lower than in controls, whereas FT4, and FT3 were normal. T4 levels in IDDM patients were positively related to T3, rT3 and TBG, and inversely related to haemoglobin Ai (HbA1. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…After purification of the subjects as a simply diabetic population, the number of the patients still counted a large number of 213. These efforts served so that the results obtained here have become more reliable with respect to the purity and scale of the subjects compared to the previous reports (Saunders, Hall and Sonksen 1978;Pittman et al 1979;Fujii et al 1981;Schlienger et al 1982;Afentoulidis and Yannatos 1982;Bernasconi et al 1984;Dorchy, Bourdoux and Lemiere 1985).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…After purification of the subjects as a simply diabetic population, the number of the patients still counted a large number of 213. These efforts served so that the results obtained here have become more reliable with respect to the purity and scale of the subjects compared to the previous reports (Saunders, Hall and Sonksen 1978;Pittman et al 1979;Fujii et al 1981;Schlienger et al 1982;Afentoulidis and Yannatos 1982;Bernasconi et al 1984;Dorchy, Bourdoux and Lemiere 1985).…”
Section: Discussionsupporting
confidence: 55%
“…It is induced mainly by decrease in the extrathyroidal conversion of l-thyroxine (T4) to T3 {Wartofsky and Burman 1982). Diabetes mellitus is one of the representative diseases which associate this syndrome as reported by Saunders, Hall and Sonksen (1978); Fujii, Akai, Tanaka, Nakatani, Kinoshita, Seki and Wada (1981) ;Schlienger, Anceau, Chabrier, North and Stephan (1982); Afentoulidis and Yannatos (1982); Bernasconi, Vanelli, Nori, Siracusano, Marcellini, Butturini and DeLuca (1984) and Dorchy, Bourdoux and Lemiere (1985) and the severity of the syndrome has been reported to correlate with the grade of hyperglycemia (Pittman, Suda, Chambers and Ray 1979;Schlienger et al 1982;Dorchy, Bourdoux and Lemiere 1988). However, hyperglycemia is just one of the clinical features of diabetes and our question in this study is that there may be another factor which affects to the serum T3 concentration in diabetes.…”
Section: Introductionmentioning
confidence: 88%
“…In a cohort of children known to have TIDM levels of serum T3, T4 and fT4 were directly related to blood pH during episodes of DKA 5. In newly diagnosed children serum T3, T4 and fT4 were inversely related to blood glucose and HbA1c3 and in non-ketotic subjects with established TIDM, serum T4 was inversely related to HbA1c 6…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that T 4 -5 deiodinase converts T4 in T3 and its activity can be inhibited by hyperglycaemia (Larsen 1982). Mean T4 levels were lower in non-ketotic diabetic children than in healthy-controls; this behaviour can be partially related to the decrease of TBG levels (Bemasconi et al 1984), as suggested by the significant correlation between T4 and TBG observed in patients with many chronic diseases (Ingenbleek, Nayer and Visscher 1979) and/or with infectious diseases (Talwar, Sawhney and Rastogi 1977;Kaptein, Grieb, Spencer, Wheeler and Nicoloff1981). Nevertheless, the concomitant T3 decrease and low serum T4 concentrations explain the presence of low rT 3 levels in pubertal non-ketotic diabetics, as previously reported (Bemasconi et al 1984).…”
Section: Discussionmentioning
confidence: 92%